Perancangan Sistem Monitoring Suhu dan Kelembaban Berbasis IoT untuk Pertanian Cerdas - I Komang Jay Yogi Ram,; I Gede Surya Rahayuda, (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2026)
The agricultural sector plays a crucial role in ensuring food security, yet it faces numerous challenges such as climate change, inefficient resource usage, and limited access to real-time data. This study proposes the design and implementation of a temperature and humidity monitoring system based on the Internet of Things (IoT) to support smart farming practices. The system uses environmental sensors connected to a microcontroller, which transmits real-time data to a cloud-based platform accessible via a web or mobile interface. By continuously monitoring environmental conditions, farmers can make more informed decisions regarding irrigation, fertilization, and pest control. The goal of this project is to increase efficiency, reduce waste, and enhance crop yields through data-driven agriculture. Testing results show that the system operates reliably in field conditions and provides accurate environmental monitoring, making it a valuable tool for modern agriculture.
Keywords: Internet of Things; smart farming; environmental monitoring; temperature sensor; humidity sensor; agriculture technology